A Decreased Level of Soluble Klotho Can Predict Cardiovascular Death in No or Mild Abdominal Aortic Calcification Hemodialysis Patients - Cai, Hong; Zhu, Xuying; Lu, Jiayue; Zhu, Minxia; Liu, Shang; Zhan, Yaping; Ni, Zhaohui; Gu, Leyi; Zhang, Weiming; Mou, Shan (Frontiers in Medicine, 2021)
Background: Soluble Klotho plays an important role in cardiovascular disease and death in chronic kidney disease (CKD). We assessed the relationship between serum soluble Klotho (sKL) level and outcome in MHD patients. Methods: Soluble Klotho was detected by ELISA. Cox regression analysis and Kaplan-Meier analysis showed the relationship between sKL and cardiovascular disease (CVD) mortality in maintenance hemodialysis (MHD) patients. Results: There were 45 cases (35.2%) of all-cause death and 36 cases (28.1%) of CVD mortality. Multivariate linear regression analysis showed that Log[iPTH] (γ = −0.224, P = 0.015) was an independent predictor of sKL level. Cox regression showed that lower sKL was associated with higher CVD mortality rate [OR = 0.401, 95% CI (0.183–0.867), P = 0.022]. Kaplan-Meier analysis showed that the CVD mortality rate increased significantly in patients with low sKL (P = 0.006). Compared with high sKL patients, low sKL patients with no or mild vascular calcification [aortic calcification score (AACs) ≤ 4] had no significant difference in all-cause mortality rate. The CVD mortality rate was significantly lower in high sKL patients (P = 0.004) than in those with low sKL. In the severe calcification group (AACs ≥ 5), all-cause and CVD mortality rates were similar between different sKL groups (P = 0.706 and 0.488, respectively). The area under the receiver-operating characteristic curve (AUC) of soluble Klotho for predicting the CVD in MHD patients with AACs ≤ 4 was 0.796 (0.647–0.946, P = 0.017), sensitivity was 0.921, and specificity was 0.50 for a cutoff value of 307.69 pg/ml. Conclusions: Lower sKL was associated with higher CVD mortality rate. Lower sKL concentration in MHD patients with no or mild calcification can predict CVD mortality.